COVID, Hoaxes and Factcheckers. Evolution of Denyings in Ibero-America 2020-2022 - Martínez-Rolán, Xabier; Dafonte-Gómez, Alberto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This text analyses the activity of factcheckers linked to the LatamChequea Coronavirus network, from January 2020 to December 2021, trying to establish the chronology, typology, thematic and origin of demented fake news on coronavirus in Latin America, to understand the phenomenon of misinformation and help to recognize new bulos if patternsare actually detected in the demented of the fake news. The results reveal that the archetype missinformation has textual format, travels through social networks at the beginning of the pandemic, and it is demented in countries with greater activity of facktcheckers.